PENINGKATAN HASIL BELAJAR TEMA 2 MUATAN MATEMATIKA MELALUI METODE BILLBOARD RANKING PADA SISWA KELAS 1SDN 18 BATU KUALI - Martri Yanti (STKIP Pesisir Selatan, 2019)
Based on the learning outcomes of Grade 1 students of SDN 18 Batu Kuali. On Thematic Learning My Love Theme found that the learning outcomes of Theme 2 Math Content is still very low. The average student learning outcomes are still below the KKM. The purpose of this study was to describe and obtain information about improving learning outcomes Theme 2 Mathematics content sub-theme 2 likes to exercise through the Billboard Ranking Method in Class 1 SDN 18 Batu Kuali Sawahlunto City. This research is a class action research. Research procedures in this study include planning, action, observation and reflection. This research consisted of two cycles with four meetings. The research subjects consisted of 15 students of Class 1 SDN 18 Batu Kuali. Research data were collected using observation sheets and daily tests. Data were analyzed using percentages. Based on the results of research and discussion that has been stated, it can be concluded that the Billboard Ranking Method can improve learning outcomes Theme 2 Mathematics content sub theme 2 likes to exercise at SDN 18 Batu Kuali. Student learning outcomes from cycle I to cycle II. Student learning outcomes in the first cycle was 57.41 (enough) increased to 84.17 (good) with an increase of 26.76%.